Micro and Macro Labor Supply Elasticities: A Reassessment of Conventional Wisdom - Keane, Michael; Rogerson, Richard (Journal of Economic Literature, 2012)
The response of aggregate labor supply to various changes in the economic environment is central to many economic issues, especially the optimal design of tax policies. Conventional wisdom based on studies in the 1980s and 1990s has long held that the analysis of micro data leads one to conclude that aggregate labor supply elasticities are quite small. In this paper we argue that this conventional wisdom does not hold up to empirically reasonable and relevant extensions of simple life cycle models that served as the basis for these conclusions. In particular, we show that several pieces of conventional wisdom fail in the presence of human capital accumulation or labor supply decisions that allow for adjustment along both the extensive and intensive margin. We conclude that previous estimates of small labor supply elasticities based on micro data are fully consistent with large aggregate labor supply elasticities. (JEL D91, E24, J22)